Characterization of Rice Black-Streaked Dwarf Virus- and Rice Stripe Virus-Derived siRNAs in Singly and Doubly Infected Insect Vector Laodelphax striatellus - Li, Junmin (Public Library of Science, 2013)

(untitled)
Replication of RNA viruses in insect cells triggers an antiviral defense that is mediated by RNA interference (RNAi) which generates viral-derived small interfering RNAs (siRNAs). However, it is not known whether an antiviral RNAi response is also induced in insects by reoviruses, whose double-stranded RNA genome replication is thought to occur within core particles. Deep sequencing of small RNAs showed that when the small brown planthopper (Laodelphax striatellus) was infected by Rice black-streaked dwarf virus (RBSDV) (Reoviridae; Fijivirus), more viral-derived siRNAs accumulated than when the vector insect was infected by Rice stripe virus (RSV), a negative single-stranded RNA virus. RBSDV siRNAs were predominantly 21 and 22 nucleotides long and there were almost equal numbers of positive and negative sense. RBSDV siRNAs were frequently generated from hotspots in the 5′- and 3′-terminal regions of viral genome segments but these hotspots were not associated with any predicted RNA secondary structures. Under laboratory condition, L. striatellus can be infected simultaneously with RBSDV and RSV. Double infection enhanced the accumulation of particular genome segments but not viral coat protein of RBSDV and correlated with an increase in the abundance of siRNAs derived from RBSDV. The results of this study suggest that reovirus replication in its insect vector potentially induces an RNAi-mediated antiviral response.